Factors of patient satisfaction in adult outpatient departments of private wing and regular services in public hospitals of Addis Ababa, Ethiopia: a comparative cross-sectional study - Demiss Mulatu Geberu; Gashaw Andargie Biks; Tsegaye Gebremedhin; Tesfaye Hambisa Mekonnen (BMC, 2019)
Abstract Background Knowing the factors for patient satisfaction is an important and direct indicator of quality of health care which is essential for providers to fill their gaps. Although few studies have been conducted on patient satisfaction in Ethiopia; but there is limited evidence for comparing patient satisfaction and associated factors in the public and private wing of the health services. Thus, this study aimed to investigate factors of patient satisfaction in adult outpatient departments in the private wing and regular services at public hospitals of Addis Ababa, Ethiopia. Methods A comparative institution based cross-sectional study was conducted from March to April 2018. A total of 955 systematically selected patients were interviewed by using an interviewer-administered structured questionnaire. Binary logistic regression analysis was performed. In the multivariable logistic regression analysis p value < 0.05 and adjusted odd ratio (AOR) with 95% confidence interval (CI) were used to identify the associated factors. Results The overall patient satisfaction was 89.3% (95% CI: 87.2-91.2). At the regular and private wings of outpatient departments it was 88.3% (95% CI: 85.4-91.2) and 90.4% (95% CI: 87.6-93), respectively. At regular service OPD, patient satisfaction was affected by female sex (AOR: 7.78; 95% CI: 2.89-20.93), long waiting time (AOR: 0.22; 95% CI: 0.07-0.73), information on the prevention of recurrent illnesses (AOR: 14.16; 95% CI: 4.58-43.83), and information on drug use and side effects (AOR: 0.22; 95% CI: 0.08-0.63). In private wing, it was affected by being in the age group of 38 to 47 years (AOR: 22.1; 95% CI: 2.39-203.6), attended elementary school (AOR: 4.69; 95% CI: 1.04-21.26), availability of drugs (AOR: 0.14; 95% CI: 0.04-0.58), and the accessibility of latrines (AOR: 6.56; 95% CI: 1.16-37.11). Conclusions Patient satisfaction at the private wing and regular adult OPDs' of public hospitals had no statistically significant difference. Female sex and information on the prevention of recurrent illnesses were factors positively affected patient satisfaction at regular services, whereas at private wing OPDs' age, attended elementary school, and accessibility of latrines were factors that positively affected patient satisfaction.